The effect of Social dominance on prejudice towards North-African minorities: Evidence for the role of social representation of Secularism as a legitimizing myth. (June 2018) - Troian, Jais; Bonetto, Eric; Varet, Florent; Barbier, Mathilde; Lo Monaco, Grégory
Abstract: Secularism in France is both a state principle and a cultural construct, that enforces a State neutrality towards religion. Recent studies have demonstrated the emergence of a lay conception called 'New Secularism' (NS) that is used to legitimize expression of prejudice towards North African minorities. However, none have been able to yet demonstrate links between NS and Social Dominance Orientation (SDO), which would further corroborate those beliefs' role as prejudice justification. Using Social Representations Theory, we created a Secularism questionnaire and used it in a cross sectional survey ( N  = 261) that also included SDO and Generalized Prejudice measures. In order to test social representation of Secularism's legitimizing function, we derived the hypothesis that NS will mediate the link between SDO and expressed Prejudice from a Social Dominance perspective. Results support our predictions and are discussed in light of intergroup status quo legitimization processes and their links with social representations.